HIGHER EDUCATION AND RURAL YOUTH: A SYSTEMATIC BIBLIOGRAPHIC REVIEW - Shakenov D. S.; Sarybayeva I. S. (Theoretical Hypotheses and Empirical Results, 2025)
Over the past two decades, access to higher education for rural youth has emerged as a critical issue in global academic and policy debates, reflecting persistent territorial and social inequalities in educational opportunities. Despite the massification of higher education systems, rural students continue to face structural barriers related to socioeconomic disadvantage, spatial isolation, and institutional arrangements. This study aims to systematically analyze international academic literature on higher education and rural youth in order to identify dominant research themes, theoretical perspectives, methodological approaches, and emerging trends over the last 20 years. The study employs a systematic bibliographic review combined with bibliometric mapping techniques. Publications were retrieved from the Scopus and Web of Science databases using a set of keywords related to higher education access, rural youth, and educational inequality. An initial search yielded 267 publications, of which 110 peer-reviewed articles were retained after a multi-stage screening and exclusion process. Thematic structures and keyword co-occurrence patterns were analyzed using the VOSviewer software. The results demonstrate a sharp increase in scholarly attention to higher education and rural youth since 2019, indicating the rapid consolidation of this research field. The literature is predominantly situated within the social sciences, while also exhibiting growing interdisciplinarity, particularly in relation to environmental studies, energy, and regional development. Thematic analysis reveals that rurality functions as a central analytical category connecting education with socioeconomic vulnerability, spatial inequality, demographic factors, and public health. The findings further highlight a geographically asymmetric research landscape, dominated by a limited number of countries, alongside increasing scholarly contributions from Kazakhstan and other transitional contexts. The study concludes that access to higher education for rural youth is increasingly conceptualized as a structural and systemic issue rather than an individual-level problem. By synthesizing fragmented research, this review provides a coherent analytical framework and identifies key research gaps, offering a foundation for future empirical studies and evidence-based policy interventions aimed at promoting equitable access to higher education for rural youth.